1991
DOI: 10.1002/bip.360310618
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and formation tendency of the cyclotetrapeptide cyclo(D‐pro‐D‐pro‐L‐pro‐L‐pro): Experimental results and molecular modeling studies

Abstract: The title compound represents the smallest member of cyclic proline peptides corresponding to the general formula c(DDLL-Pro4)n with a strictly D,D,L,L double-alternating sequence of the chiral amino acid residues. The cyclopeptides with n greater than or equal to 2 could be synthesized from both DDLL-Pro4 (1) and DLLD-Pro4 (2). The cyclic monomer (n = 1) resulted only from 2, whereas not even a trace could be found by cyclization of 1. The peptide exists in a strongly strained Ci symmetrical conformation (x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This indicated that 6a and 6b , presumed to be cyclic peptides, were hydrolyzed. While the ring opening of cyclotetrapeptides has been reported to occur under relatively mild hydrolytic conditions [TFA/H 2 O (8:2), 5 h, r.t.],[15a] there is no precedent for cyclotetrapeptides to undergo ring opening under slightly acidic conditions such as those used in RP‐HPLC (mobile phase consisted of 0.1 % TFA in H 2 O/MeCN mixtures). Furthermore, attempts to isolate 6a and 6b either by RP‐HPLC under neutral conditions or by silica‐gel chromatography failed, even if the purification was performed at low temperatures (e.g., 5 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that 6a and 6b , presumed to be cyclic peptides, were hydrolyzed. While the ring opening of cyclotetrapeptides has been reported to occur under relatively mild hydrolytic conditions [TFA/H 2 O (8:2), 5 h, r.t.],[15a] there is no precedent for cyclotetrapeptides to undergo ring opening under slightly acidic conditions such as those used in RP‐HPLC (mobile phase consisted of 0.1 % TFA in H 2 O/MeCN mixtures). Furthermore, attempts to isolate 6a and 6b either by RP‐HPLC under neutral conditions or by silica‐gel chromatography failed, even if the purification was performed at low temperatures (e.g., 5 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, even for linear peptides containing several turn‐promoting amino acids, the success of cyclization is still sequence dependent . For instance, the cyclo( d Pro‐ d Pro‐Pro‐Pro) peptide can only be obtained upon starting from H‐ d Pro‐Pro‐Pro‐ d Pro‐COOH …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, DLDLDL-Pro6 cyclizes at high dilution ( < 0.00 1 M ) with -80% yield of the hexaprolyl ring and 9% dimer; but at 0.0 1 M concentration, the monomer yield decreases to 3%, with 7% dimer and more than 70% of polymeric material. 23 The low yield of oligomeric ring formation at moderate concentration can be ascribed to a relatively stable helical conformation of the linear intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the area of structural modeling have increased our ability to design bioactive cyclic peptides and peptidomimetics, yet the cyclization step in the actual synthesis is often troublesome, particularly for head‐to‐tail cyclization of small (< 7 residues) peptides (5). Several cases have been reported in the literature in which cyclization yields depend strongly on the sequence of the linear peptide precursor (5–9). Moreover, several linear precursors, all leading to the same cyclic product, often showed highly variable yields in the cyclization (7–9).…”
mentioning
confidence: 99%
“…Several cases have been reported in the literature in which cyclization yields depend strongly on the sequence of the linear peptide precursor (5–9). Moreover, several linear precursors, all leading to the same cyclic product, often showed highly variable yields in the cyclization (7–9).…”
mentioning
confidence: 99%